Google’s Open Source and Interests of Internet Users on Searching It - Maharani, Anita (Bina Nusantara University, 2018)
This article starts with a discussion on why open source is important, especially for education. Although open source develops for all kinds of matter, but for education it will deliver long term effect for the society. Open source, has two types, one is offered in cheaper price, and other is offered in free of purchasing price, and we know it as Free and open source software (FOSS). Frankly, FOSS is part of technology and knowledge transfer and development to support Global Goals Part 17. Google, has role in FOSS development, and FOSS is as their spirit. When Google first launched their Open Source initiatives openly through opensource.google.com, it is interesting to see what are products that they offer to the society, and since Google is an internet-based information technology company, then we use Google Trends to see interests of internet users on searching for Google’s Open Source. To support this research, we use Google Trends as our research tool, among several information given in Google only information’s that related with user’s interest that will be continue for discussion. Results shows that recently only two countries that show strong interest in Google’s Open Source, they are India and United States. It can also be argued that although Google has been established for more than 10 years as it may be accessible to internet users as society, but Google still need to find ways to promote opensource.google.com to larger numbers of internet users, this resulted when writer tries to compare between Google’s Open Source as keyword and Open Source as keyword, where Open Source as keyword have highest interest user in aggregate.